Human resources study in nutrition, dietetics, and home economics : an update - Warner, Eunice (CFNI KingstonJM, 1987)
Surveys the Caribbean's nutrition, dietetics, and home economics scene noting number of persons and kinds of programs in each area, the tertiary levels of training, and the extent of employment for trained personnel in the three areas. Reviews opinions on the introduction of a Bachelor's Degree Programme in these areas at UWI. Discusses training facilities/programmes, and needs in the above subject areas. Makes recommendations relating to the health, education, agriculture and other sectors, the Bachelor's degree and dietetic internship programmes, and follow up study.